Electroacupuncture Improves Antidepressant Effects in CUMS Rats by Protecting Hippocampal Synapse and Mitochondrion: An Ultrastructural and iTRAQ Proteomic Study - Zhang, Jialing (Evid Based Complement Alternat Med, 2019)
Electroacupuncture (EA) is considered a complementary therapy for depression. Trials also found that EA has additive benefits when combined with medication compared with medication alone. It is revealed that EA restores altered hippocampal synaptic plasticity in depressed brain. But precise molecular mechanism is poorly understood. Here, we evaluated the therapeutic effects of EA and EA combined with selective serotonin reuptake inhibitor (SSRI) on depressed (CUMS) rats. Then a new proteomics approach, isobaric tag for relative and absolute quantitation (iTRAQ), was used to explore the differential expressed synaptic protein in hippocampus between CUMS and EA-treated rats to identify the possible target molecular mechanism of its effects. We found that EA had additive benefit against depressive behaviors when combined with SSRI. Ultrastructure study on neuron showed significant change in postsynapse density (PSD) and mitochondrion. Through iTRAQ, it is found that synaptic and mitochondrial proteins were significantly changed after EA, consisting with ultrastructure study results. These findings suggest that EA improves antidepressant performance in depressed rats through protecting synaptic and mitochondrial functions in hippocampus.